Analysis of Molecular Genetic Markers of Osteoporosis in Residents of the Russian Federation - R. V. Polibin; A. V. Lomonosova; E. V. Glushkova; A. G. Chigir; M. I. Pugachev; G. N. Hohlov; I. S. Bakutin (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. Osteoporosis is a multifactorial disease with a high level of disability, which is a serious health problem worldwide. High prevalence and disability rates are associated not only with the peculiarities of the course of this pathology, but also with the untimely diagnosis and initiation of therapy. Therefore, it is extremely relevant to search for specific and accessible markers of osteoporosis, such as molecular genetic markers or single-nucleotide polymorphisms, analysis of which will help identify risk factors for disease development before clinical symptoms manifest during patient examinations.Aims. This study is aimed at finding risk factors for the development of HCG in patients with gastritis and the relationship of polymorphisms of various genes with the development of this pathology.Materials and methods. A search was made for the association with osteoporosis of singlenucleotide polymorphisms of the genes: COL1A1, CYP2R1, ESR1, LCT, LRP5, VDR in residents of the Russian Federation (n = 669). Polymorphic markers of candidate genes were selected for research based on the presence of associations with osteoporosis according to previously conducted studies published in the RSCI, PubMed, Web of Science, MEDLINE, Scopus databases, as well as on the results of monitoring polymorphisms included in the panels of genetic predisposition to osteoporosis of companies engaged in genetic testing in the Russian Federation. Two groups were formed for the study: the main (case) – 234 patients with an established diagnosis of Osteoporosis, the control – 435 patients selected using a random number generator from conditionally healthy individuals from the Basis Genomic Group database (Basis Genomics LLC). The groups were comparable in age and gender (p > 0.05).Statistical analysis was carried out using the StatTech v. 3.1.6. program (developed by Stattech LLC, Russia). The nature of the distribution of quantitative data was checked by the Shapiro-Wilk, Kolmogorov-Smirnov criteria, the statistical significance of differences in 2 independent groups was assessed using the Mann-Whitney U-test. The ꭓ2 Pearson criterion was used to evaluate the associations of alleles of selected genes with the risk of osteoporosis.Results and discussions. Analysis of the maps of 669 patients showed that for residents of the Russian Federation, the polymorphism rs3736228 of the LRP5 gene can be used as a genetic marker of osteoporosis, since there were significant differences in the frequency of occurrence of CT and TT allele variants in the group of patients with osteoporosis and in the control group. Results of studies of single-nucleotide polymorphisms COL1A1_rs1800012_G/T, CYP2R1_rs10741657_A/G, ESR1_rs2234693_C/T, ESR1_rs9340799_A/G, LCT_rs4988235_C/T, VDR_rs1544410_A/G, VDR_rs2228570_C/T in residents of the Russian Federation The federations did not show significant differences between the groups, therefore, in the future, the results of studies of these polymorphisms to assess the risk of osteoporosis in patients should be evaluated with caution.Conclusions. According to the results of the study conducted on residents of the Russian Federation, only one of the eight alleles in candidate genes for the risk of osteoporosis showed a significant relationship in patients in the Russian Federation. It has been shown that variants of TT and CT polymorphism rs3736228 of the LRP5 gene are the risk genotype for osteoporosis.